Governance mechanisms and firm performance in family-owned companies in Malaysia / Azmi Abd. Hamid, Rozainun Abdul Aziz and Asyifa Laila Hosni - Abd. Hamid, Azmi; Abdul Aziz, Rozainun; Hosni, Asyifa Laila (Research Management Institute (RMI), 2014)
The study examines the relationship between management and governance mechanisms upon the performance of family-owned companies. The results indicated that the performances of family-owned companies' were influenced by the implementation of corporate governance in their management processes. Hence, the result reveals a significant association between family-owned companies' performance in relation to management and governance mechanisms. However, the findings found that Malaysian family-owned companies may be reluctant to protect the minority shareholders’ rights as the findings show that the independent directors portrayed significant negative association with the firm’s performance. The presence of the independent directors in the company could not improve the monitoring of the management activities and on shareholders' influence. In addition, the ROE result shows that the larger managerial ownerships, the higher the firms' performance but in turn it will heighten the minority shareholders' expropriation. The higher level of managerial.